Sociology of Education: Exploration of Stakeholders Experiences of Inclusive Education in Schools - Abdul-Jaleel Saani (IAFOR Journal of Education)
The study explored lived experiences of major stakeholders with regard to Inclusive Education (IE) practices in mainstream public basic schools using heuristic inquiry of descriptive phenomenological approach. The sampled participants were selected using purposive sampling technique. Six set of semi-structured interview guides were used to collect the data. The data were manually analysed reflexively using Braun and Clarke six-phase model of thematic analysis. The study revealed that there is some level of misconception about IE on the part of stakeholders. Also, these stakeholders have malfunctional experiences regarding their lived experiences of IE practices in schools. Nevertheless, when teachers are able to employ innovative, gender and culture responsive instructional strategies that take into consideration the sociocultural and Special Education Needs and Disabilities differentials of learners, they will be able to ensure inclusion of all learners. Regular organisation of in-service trainings to stakeholders, particularly those in the working and lower classes, regarding the conceptualisation and practices of IE based on our IE policies and laws will help in ensuring that we educate all learners in well-integrated school settings.